Immune Checkpoint Blockade in Melanoma – Earlier is Better? - Vincas Urbonas; Audrius Dulskas; Edita Baltruškevičienė; Daiva Dabkevičienė (Acta Medica Lituanica)
Administering checkpoint inhibition before surgery, known as neoadjuvant therapy, shows promise in treating bulky yet resectable melanomas, and researchers are investigating its potential in various other cancer types. This approach boasts a considerable success in high pathologic response rate, a factor directly linked to survival rates. The routine availability of biopsies presents a distinct chance to comprehend treatment responses. Neoadjuvant ICIs offer advantages like T cell expansion, treatment assessment through surgical specimens, and potential tumor size reduction for better surgical outcomes. However, further research is needed to optimize patient selection and treatment protocols.